2008
DOI: 10.1159/000111725
|View full text |Cite
|
Sign up to set email alerts
|

Modified Transurethral Incision of the Bladder Neck Treating Primary Bladder Neck Obstruction in Young Men: A Method to Improve Voiding Function and to Preserve Antegrade Ejaculation

Abstract: Objectives: To evaluate the voiding function, ejaculation status and sexual function after the novel modification of transurethral incision of the bladder neck (TIBN) treating young men with primary bladder neck obstruction (PBNO). Methods: Using a videourodynamic study, PBNO was diagnosed in 33 young men 27–50 years of age who presented with chronic lower urinary tract symptoms and low urinary flow. TIBN was performed in all patients, with the modification of preserving a portion of the supramontanal tissue d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The TUIBN has the advantage of sustained long‐term benefit without the need of re‐do procedures. However, the main concern with this invasive treatment is the development of retrograde ejaculation in 11–27% of patients, although modifications of the technique have been reported to allow avoiding this troublesome dysfunction . Significant risk of reduced sperm counts has been reported also after modified, unilateral TUIBN …”
Section: Discussionmentioning
confidence: 99%
“…The TUIBN has the advantage of sustained long‐term benefit without the need of re‐do procedures. However, the main concern with this invasive treatment is the development of retrograde ejaculation in 11–27% of patients, although modifications of the technique have been reported to allow avoiding this troublesome dysfunction . Significant risk of reduced sperm counts has been reported also after modified, unilateral TUIBN …”
Section: Discussionmentioning
confidence: 99%
“…In younger patients with LUTS and a small TPV, BND or PRES could be responsible for the LUTS. Surgical intervention should be carefully considered in patients with PRES while transurethral incision of the prostate may be adequate to preserve ejaculatory function in these young men . On the other hand, in older patients with a small TPV, diagnosis of DO, DU or DHIC should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention should be carefully considered in patients with PRES while transurethral incision of the prostate may be adequate to preserve ejaculatory function in these young men. 19 On the other hand, in older patients with a small TPV, diagnosis of DO, DU or DHIC should be considered. Surgical intervention such as TURP should be carefully evaluated when treatment with alpha-blockers has failed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…82 In a study of men who had undergone BNI for outflow obstruction rather than PUV, 47 of 61 men retained normal antegrade ejaculation, although reduced semen volume was noted in 11 men and retrograde ejaculation in three. 83 Yang et al 84 reported antegrade ejaculation in all 32 patients who underwent the modi fied BNI procedure (ending 0.5-1.0 cm proximal to the verumontanum). Consistently, no difference in sexual function or paternity rates were found in our study of men with PUV who had or had not undergone BNI.…”
Section: Sexual Functionmentioning
confidence: 99%